Effect of densified oil palm empty fruit bunch towards the torrefaction process - Pang, Zee Yee (2015)
Biomass refers to raw organic material from plant or animal is used to generate a number of energy resources which convert chemical energy to heat energy through combustion. Oil palm empty fruit bunch (EFB) is one of the biomass which has high moisture content and very bulky in term of storage. Thus, this study is to upgrade the EFB waste to a valuable biofuel using pelletization and torrefaction processes. The pelletization process able to remove the moisture content of raw EFB, increase the energy content and easy for storage. In this study, different ratio of EFB and starch will be made to test the effect of ratio on the quality of biofuel produced. Torrefaction process is a process which the EFB will be heated in an inert atmosphere at temperature of 250°C. The EFB will have higher energy content, lower moisture content and higher stability in storage of EFB. The torrefied EFB pellets will undergo characterization to determine the optimum ratio of EFB and starch. The calorific value of the torrefied EFB pellet is measured by using bomb calorimeter. The lowest and the highest calorific values are 19.69MJ/kg for no starch content and 20.02 MJ/kg for 15% starch content EFB pellets. The mass yield of EFB pellet after torrefaction process is about 81% to 84% which increases directly proportional to the starch content in the EFB pellets. The highest energy yield of torrefied EFB pellet is 90.54% while the lowest is 85.59% which is the pellet with no starch content. The fourier transform infrared spectroscopy (FTIR) analysis analyzed the components such as starch, lignin, hemicelluloses and cellulose in the torrefied EFB pellets as compare to the raw EFB. As a conclusion, 10% starch content EFB pellet is the optimum condition because it has the calorific value, energy yield and mass yield which are approximately same as the 15% starch content EFB pellet.